Escola Doméstica de Nossa Senhora do Amparo e o processo de escolarização de mulheres negras na Primeira República (1889 – 1910) - Leal, Luciana Silva (2017)
The present work aims to analyze the history of Escola Doméstica Nossa Senhora do Amparo – an institution dedicated to underprivileged girls running uninterruptedly since the nineteenth century up to the present day – and the schooling process of black students at the beginning of the Republican period. Founded in 1871 by João Francisco de Siqueira Andrade, a.k.a Father Siqueira, in the municipality of Petrópolis, the school’s main goal was to protect and educate orphans of war and also the naive ones, a term used to designate the free children born of enslaved mothers from the promulgation of the Free Womb Law in September 1871. This research investigated Padre Siqueira’s enterprise portraying its work of building a sociability network (SIRINELLI, 1996) through religion, which guaranteed the survival of the institution. It also sought to describe the moral standards which governed the role of women in Brazil in the early years of the Republic and how that reflected on female education. Aiming to understand how the schooling of black women in the Republican period occurred, as investigation was done on who were the students who attended the Domestic School at that time, where they came from and what learning content they had access to. The sources used were the documentation provided by the school, periodicals and reference bibliography related to the school and its principals